Plan and analysis of synchronous buck converter for UPS application - Sreedhar, Jadapalli; Basavaraja, B (International Journal of Engineering and Technology, 2017)
DC-DC converters occupies very significant role in the field of industries or daily life applications. To charge batteries of low voltage connected to uninterrupted power supply (UPS), DC-DC converters are needed. Batteries requires low voltage and the available voltage at the source is to be step-down to the required level of voltage at the point of utility (PoU). While designing DC-DC converters, efficiency and simplicity of the circuit is very much important. Simply for the UPS applications, Buck converter can deliver the voltage at required level which is very simple in operation but the increased losses in diode can be addresses by using a synchronous Buck converter. By using synchronous Buck converter, the diode conduction losses in Buck converter can be minimized, thus improving the efficiency of the converter. In this paper, Synchronous Buck converter is used to charge the batteries of UPS. In this paper Design, modeling of synchronous Buck converter for UPS application was done and its results were obtained by using Matlab/Simulink. A hardware prototype was also developed and the hardware results were also shown.Â Â